Educating the educators: Implementing cultural safety in the nursing and midwifery curriculum. (October 2022) - Best, Odette; Cox, Leonie; Ward, Aletha; Graham, Coralie; Bayliss, Luke; Black, Barbara; Burton, Lucinda; Carey, Melissa; Davis, Teresa; Derrington, Kate; Elliott, Jessie; Jayasinghe, Thenuja; et al.
Abstract: Background: The Australian Nursing and Midwifery Accreditation Council mandates the teaching of cultural safety in Bachelor of Nursing and Midwifery programs in Australia. However nursing and midwifery academics may lack the awareness and knowledge required to share and develop cultural safety practices with their students. Specific cultural safety professional development for academics may be needed. Objectives: This research explores how nursing and midwifery academics at an Australian university understand cultural safety and whether they are equipped to embed it in the curriculum. It also examines whether professional development workshops can support academics to prepare for cultural safety. Methods: An intervention involving three cultural safety professional development workshops was offered to nursing academics at an Australian university. The authors used qualitative surveys to consider whether the workshops deepened participants' understanding of cultural safety and developed the self-reflection required to embed cultural safety in teaching. Results: The workshops contributed to participants' improved understandings of culture, colonisation, white privilege and the need for self-reflection, but not all participants developed a working knowledge of cultural safety practice. Conclusion: Professional development workshops can assist nursing and midwifery academics to develop their knowledge of cultural safety, but detailed, contextual understanding is likely to need more than three sessions. Academics' motivations to include cultural safety in their teaching may be linked to their desire for patient-driven and equitable services and a desire to meet accreditation requirements. Highlights: What is currently known? Cultural safety must be embedded in the nursing and midwifery curriculum across Australia. What the paper adds. This paper describes cultural safety professional development for academics, with surveys to understand its effects. Application for practice? Cultural safety PD is a way to educate the educators for implementing mandated curriculum.